P33 Pharmacological stimulation of HIF signalling as a potential treatment approach for the type 2 diabetic heart. (21st March 2018) - Sousa Fialho, MdL; Kerr, M; Dodd, MS; Montes Aparicio, C; Tyler, DJ; Heather, LC
Abstract : Introduction: In response to ischemia, type 2 diabetic hearts are less able to upregulate anaerobic glycolysis and show poorer contractile function. Pharmacological activation of Hypoxia-Inducible Factor (HIF) may be beneficial for the diabetic heart, as it may promote glycolysis, improve function and tolerance of ischaemia. Methods: Control and type 2 diabetic rats were given five oral doses (5 mg/kg daily) of PHD-selective HIF activator BAY85–3934. Hearts were perfused ex vivo and subjected to low-flow (0.35 ml/min/gww) ischaemia-reperfusion (IR). Glycolysis, palmitate oxidation and function were measured throughout. Mitochondrial oxidation was measured in isolated mitochondria using a Clark-type electrode. Results: Diabetic hearts showed decreased rate-pressure product following ischaemia-reperfusion. Pre-treatment with BAY85–3934 resulted in increased glycolytic rate in diabetic hearts, paired with improved functional recovery post-IR. BAY85–3934 treated diabetic rats showed increased hematocrit, indicating systemic activation of HIF signalling. Blood glucose levels remained unchanged with treatment despite changes in cardiac glycolytic rate. Conclusion: This study has shown that treatment with HIF activators may provide a novel avenue to improve metabolism and functional recovery in the diabetic heart following ischaemia-reperfusion.